Stability of equilibria of a predator-prey model of phenotype evolution - Sílvia Cuadrado (Mathematical Biosciences and Engineering)
We consider a selection mutation predator-prey model for the distribution of individuals with respect to an evolutionary trait. Local stability of the equilibria of this model is studied using thelinearized stability principle and taking advantage of the(assumed) asymptotic stability of the equilibria of the residentpopulation adopting an evolutionarily stable strategy.